Characteristics of polarization of geomagnetic sudden commencements at geostationary orbit - Nagano, Hiroshi; Araki, Tohru; Fukunishi, Hiroshi; Sato, Natsuo (1985)
P(論文) Local time dependence of polarization of geomagnetic sudden commencements (SC's) at geostationary orbit was statistically analyzed, using magnetic data from GOES 2 and 3 satellites for the interval from August 1978 to August 1980. The polarization in the plane perpendicular to the geomagnetic field is counterclockwise in the morning side and clockwise in the afternoon side, when viewed along the field direction. The demarcation line across which the polarization is reversed seems to be located between 11h and 14h LT. This time span may be due to different angles at which shock fronts or discontinuities propagating in interplanetary space collide against the magnetosphere. The latitudinal reversal of polarization of SC observed in high latitudes on the ground does not seem to occur at geostationary orbit. departmental bulletin paper